Implementation of Performance Management to Employees at Happy Family KTV Tanjungpinang - Syarafina, Dhea Tiur; Chandra, Dwi Suci Ananda; Hia, Herti Tri Nurhayati; Satriadi (International Journal of Asian Business and Management, 2023)
Implementing performance management for employees at Happy Family KTV is an important strategy to achieve company goals, improve service quality and maximize customer satisfaction. This research aims to examine the effectiveness of implementing employee performance management at Happy Family KTV, as well as what strategies can be implemented to improve employee performance. The methods used in this research include literature study, observation and interviews. The research results show that implementing performance management at Happy Family KTV involves several stages including performance planning, performance measurement, and performance evaluation. Apart from that, this company also implements a reward and sanction system to motivate employees. Data analysis shows an increase in service quality and customer satisfaction along with the implementation of effective performance management. Strategies that can be used to improve employee performance include training and competency development, providing resource support, and effective communication between management and employees. In conclusion, the implementation of performance management for employees at Happy Family KTV has had a positive impact on service quality and customer satisfaction. Companies need to continue to implement effective strategies to manage employee performance in order to face the challenges of business competition in the future